NUTRITIONAL-CONSTITUTIONAL OBESITY - Jumanazarova Mokhinur Jumanazar kizi (Journal of Medical Genetics and Clinical Biology, 2024)
this article is devoted to such a topic as obesity, its symptoms and prevention.